“Belajar Mandiri” Peran Perpustakaan Perguruan Tinggi Dalam Mendukung Tugas Pokok Dan Fungsi Program Studi - Nanik Rahmawati (Pusat Publikasi Ilmiah UIN Fatmawati Sukarno Bengkulu, 2017)
In order to realize the task, principal and function and vision of the University's mission, one of the main supporters is the existence of a credible library. Librarians who are in the library of the University should have thoughts, insights, understand the vision and mission goals and objectives of the University. The role of libraries will be more strategic, can achieve goals and more easily developed when 5 (five) basic principles of library law carried out in an orderly manner, namely; Book are for use; Every reader his / her book, Every book readers, Save the time of the readers; Library its growing organism. In order for the existence of the library can be utilized optimally, the librarian should also be provided either soft skill or hard skills